Removal of methyl orange from contaminated water by newly prepared nickel catalyst - Fatin Mardhiah Nordin (2017)
Contaminated water can cause by industries and anthrpogenic activities. Nowadays, the communities faced water problems due to the usage of dyes in industries and it was an urgent need to overcome this problem using cheaper catalyst such as nickel. The research was done to characterize the prepared tannin chitosan nickel doped catalyst and to evaluate the catalytic activity of the newly prepared catalyst in the oxidation of methyl orange. The nickel catalyst was prepared by dry impregnation method and characterized by different techniques such as using Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). From the FTIR spectrums,the shift in OH and NH peaks in nickel catalyst indicated the involvement of OH and NH groups binding with the nickel. From the SEM, the tannin chitosan support has a smooth surface and the nickel was supported on the tannin chitosan support when the nickel was dropped on the support. The XRD spectrums showed both tannin chitosan support and nickel catalyst were an amorphous phase with a monoclinic crystal system. The catalytic activity was carried out in three different temperatures (313, 323 and 333 K) and observed by degradation percentage of methyl orange. The highest degradation percentage of catalytic activity was at 313 K as the degradation efficiency was at maximum.